Comparative analysis of gastric cancer risk attribution (1990-2021) and 2050 burden projection in China, Japan, and South Korea: an age-period-cohort modeling approach based on the Global Burden of Disease 2021 study - Jiang, Tao; Tan, Liming; Dai, Kehang (Frontiers in Oncology, 2026)
BackgroundGastric cancer (GC) is the fifth most common cancer and fourth leading cause of cancer-related death globally, with a particularly high burden in East Asia. Significant differences exist among China, Japan, and South Korea in terms of risk factor exposure, screening practices, and demographic shifts, yet existing research lacks cross-national comparisons of long-term trends and quantitative analyses of policy effectiveness; this study aims to systematically analyze the spatiotemporal evolution of GC burden in these three countries from 1990 to 2050 by integrating the Global Burden of Disease (GBD) 2021 database with the Bayesian Age-Period-Cohort (BAPC) model to provide evidence for Asia-Pacific prevention and control strategies.MethodsWe extracted data on key GC epidemiological indicators—including age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years rate (ASDR)—as well as relevant risk factor data from 1990 to 2021 using the GBD 2021 database. An enhanced Age-Period-Cohort (APC) analytical framework was adopted, and log-linear models were constructed to quantify the independent impacts of age, period, and cohort effects on GC burden. The population attributable fraction (PAF) method was applied to estimate the proportion of DALYs attributable to modifiable risk factors such as smoking and high-sodium diets. For trend projection (2022–2050), the BAPC model was utilized, forming a comprehensive analytical chain that spanned data extraction, effect decomposition, and future burden forecasting.ResultsFrom 1990 to 2021, age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years rate (ASDR) of GC declined significantly across China, Japan, and South Korea. The absolute burden trends differed among the three countries: new GC cases in China increased from 300,000 in 1990 to 612,000 in 2021, with annual deaths reaching 445,000; Japan and South Korea had 9% and 7% reductions in new cases, respectively, along with substantial declines in mortality. Risk attribution analysis showed that smoking was the primary factor associated with GC burden among males in China, while high-sodium diets were the dominant associated factor in Japan and South Korea. South Korean women aged 20–49 had a higher incidence rate than their male peers (relative risk [RR] = 1.23). Decomposition analysis identified adults aged ≥65 years as the main burden group: this age group contributed 60%–70% of ASIR and ASMR in China, 55%–65% in Japan, and 50%–60% in South Korea. After 2000, the contribution of period effects to ASMR continued to decrease across the three countries. Later birth cohorts (post-1970) had significantly reduced GC risk: compared with pre-1950 cohorts, post-1970 cohorts in China had a 20% lower ASIR (reflected in a 16% lower risk among 30–34-year-olds), and South Korea’s post-1970 cohorts had a 30% reduction (manifested as a 58% lower risk in the 50–54 age group). Projections to 2050 indicated that ASIR and ASMR will continue to decline across the three countries, with China’s ASIR ≈17/100,000 and ASMR ≈8/100,000, and Japan and South Korea’s ASIR ≈8–9/100,000. China’s absolute GC burden will remain higher than that of Japan and South Korea, driven by population aging and the persistent impacts of smoking and high-sodium diets.ConclusionsThis study finds that from 1990 to 2021, ASIR, ASMR, and ASDR of GC in China, Japan, and South Korea showed a marked decline, yet absolute disease burdens differed. China’s burden remained heavy due to its large population and rapid aging, while Japan and South Korea made substantive progress via efficient screening. Risk attribution analysis revealed smoking as China’s main risk factor and high-salt diets as more impactful in Japan and South Korea. Projections suggest a continued decline in disease burden in all three countries by 2050.